The Cholinergic Anti-Inflammatory Response and the Role of Macrophages in HIV-Induced Inflammation - Delgado-Vélez, Manuel (Int J Mol Sci, 2018)
Macrophages are phagocytic immune cells that protect the body from foreign invaders and actively support the immune response by releasing anti- and proinflammatory cytokines. A seminal finding revolutionized the way macrophages are seen. The expression of the neuronal alpha7 nicotinic acetylcholine receptor (α7-nAChR) in macrophages led to the establishment of the cholinergic anti-inflammatory response (CAR) in which the activation of this receptor inactivates macrophage production of proinflammatory cytokines. This novel neuroimmune response soon began to emerge as a potential target to counteract inflammation during illness and infection states. Human immunodeficiency virus (HIV)-infected individuals suffer from chronic inflammation that persists even under antiretroviral therapy. Despite the CAR’s importance, few studies involving macrophages have been performed in the HIV field. Evidence demonstrates that monocyte-derived macrophages (MDMs) recovered from HIV-infected individuals are upregulated for α7-nAChR. Moreover, in vitro studies demonstrate that addition of an HIV viral constituent, gp120(IIIB), to uninfected MDMs also upregulates the α7-nAChR. Importantly, contrary to what was expected, activation of upregulated α7-nAChRs in macrophages does not reduce inflammation, suggesting a CAR disruption. Although it is reasonable to consider this receptor as a pharmacological target, additional studies are necessary since its activity seems to differ from that observed in neurons.